Intellectual capital, green innovation, and financial performance: The mediating role of sustainability - Dwiputri, Rachmaniar Myrianda; Suyono, Eko; Laksana, Rio Dhani (International Journal of Management and Sustainability, 2023)
This research aims to find out how internal resources, intellectual capital, and green innovation in West Java's creative industries can improve small businesses financial performance. Besides, this research also examines the sustainability of small businesses in mediating the effect of intellectual capital and green innovation on financial performance. The research sample consists of 335 respondents who are owners and creative industry workers in West Java, Indonesia. The data were collected using a questionnaire and analyzed using Structural Equation Modeling (SEM). The results indicate that Intellectual Capital (IC ) and green innovation improve financial performance and sustainability. This research establishes a mediator role for sustainability in the interaction between intellectual capital, green innovation, and financial success. This study demonstrates the significance of sustainability in helping small businesses achieve high financial performance. This study highlights the significance of integrating sustainability practices inside the small business sector to optimize revenues through the utilization of internal resources, including intellectual capital and green technologies. This study offers practical implications for small businesses in Indonesia, suggesting that sustainability should be implemented to improve financial performance.